84 Cardiovascular Risk Reduction Using Contemporary Guideline Recommendations: Outcomes of the Heart Attack Prevention Programme for You (Happy) London Study. (3rd June 2016) - Khanji, Mohammed; Balawon, Armida; Boubertakh, Redha; Petersen, Steffen
Abstract : Introduction: Cardiovascular disease (CVD) remains the leading cause of morbidity and mortality globally. The importance of primary prevention (PP) of CVD is now well recognised and can potentially improve quality of life and survival cost-effectively. Aim: To assess benefits of contemporary guideline based PP recommendations for CVD risk reduction in those with elevated global cardiovascular risk. Methods: 402 participants aged 40–74 years were recruited as part of the HAPPY London study. Eligible participants had an elevated 10-year risk based on a QRISK2 score of 10% or more. Internet access was required to be able to register and complete questionnaires online. Individualised one-off cardiovascular risk reduction advice was provided, based on the JBS3 and ESC 2012 CVD prevention guidelines. Follow-up at 3 months assessed changes in risk factors and risk scores using paired t-test statistical analysis. Results: Mean age 65 years; 37% females and 370 (92%) completed the 3-months follow up. There was a small but significant improvement in mean blood pressure from 132/80 mmHg to 129/78 mmHg (p < 0.001). Other improvements included weight, waist circumference, fasting glucose, total cholesterol, physical activity, Framingham and QRISK2 scores (Table 1). QRISK2 score dropped from 18.9% to 18.5% at follow-up. This was a 0.7% absolute reduction compared to expected resulting in about 660 less CVD events per 100, 000 over 10 years. Conclusions: Implementing guideline recommendation for CVD PP can produce modest improvements in risk factors in the medium term in patients at high cardiovascular risk. Promoting long-term compliance should help lower future cardiovascular events.